Comparative Research on Romanian SMEs Crediting - Florin - Mihai MAGDA; Adina Elena DANULETIU (Hyperion Economic Journal, 2014)
In an efficient market economy, economic growth and welfare is based on the existence of a powerful SME sector. As proven in the context of the nowadays crisis, a powerful and well-developed SME sector can successfully cope with economic challenges and can adapt more easily to a negative economic context, insuring, in the same time, the premises for the economic recovery and the population welfare. Therefore, one of the most important concerns for the developing countries is the development of the SME segment, which obviously supposes the accumulation of capital. Considering the post-revolutionary economic history of Romania, the shift from a centrally planned economy to the market economy, and afterwards the financial crisis that has started in 2008, at present the SME segment is being developed especially through loans granted by the commercial banks, taken into account the low absorption rate of European funds and the insignificant and incoherent governmental financing programs. Therefore, this paper is important and actual as it synthetically and relatively simply presents the way in which Romanian commercial banks determine which SMEs may be financed, after performing a quantitative / financial analysis of the applicants in order to correctly determine the credit risk as a result of assessing and interpreting the main economic and financial indexes. We will also present the actual macro-economical stage (crediting terms, credit risk, credit demand, etc), as well as the main similarities and differences occurring in the SMEs crediting process at the Romanian commercial banks.